When Credit Dries Up: Job Losses in the Great Recession - Samuel Bentolila; Marcel Jansen; Gabriel Jiménez; Sonia Ruano (Center for Economic Studies and ifo Institute (CESifo), 2013)
We use a unique dataset to estimate the impact of a large credit supply shock on employment in Spain. We exploit marked differences in banks' health at the onset of the Great Recession. Several weak banks were rescued by the State and they reduced credit more than other banks. We compare employment changes from 2006 to 2010 at firms heavily indebted to weak banks before the crisis and the rest. Our estimates imply that these firms suffered an additional employment drop between 3 and 13.5 percentage points due to weak-bank attachment, representing between 8% and 36% of aggregate job losses.
Keywords: D92; G33; J23; 330; job losses; Great Recession; credit constraints